2016
DOI: 10.1097/pas.0000000000000736
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Grading of Prostatic Adenocarcinoma Can Be Further Optimized

Abstract: Histologic grading remains the gold standard for prognosis in prostate cancer, and assessment of Gleason score plays a critical role in active surveillance management. We sought to optimize the prognostic stratification of grading and developed a method of recording and studying individual architectural patterns by light microscopic evaluation that is independent of standard Gleason grade. Some of the evaluated patterns are not assessed by current Gleason grading (eg, reactive stromal response). Individual his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(48 citation statements)
references
References 60 publications
3
39
0
Order By: Relevance
“…There was no significant difference in the expression of AR in normal or tumor samples (p>0.05); however, higher AR expression was associated with a shorter survival time, compared to low expression of AR (p>0.05). Across cancer subgroups (Gleason scores=6, 7,8,9,10), in the high AR expression group, the group with Gleason score=10 had the shortest survival. The low/medium AR expression group had similar results, those with Gleason score=10 had the shortest survival, when compared with other groups (p<0.05) (Figure 4).…”
Section: Prostate Adenocarcinoma Data Analysis Using Tcga Databasementioning
confidence: 97%
See 1 more Smart Citation
“…There was no significant difference in the expression of AR in normal or tumor samples (p>0.05); however, higher AR expression was associated with a shorter survival time, compared to low expression of AR (p>0.05). Across cancer subgroups (Gleason scores=6, 7,8,9,10), in the high AR expression group, the group with Gleason score=10 had the shortest survival. The low/medium AR expression group had similar results, those with Gleason score=10 had the shortest survival, when compared with other groups (p<0.05) (Figure 4).…”
Section: Prostate Adenocarcinoma Data Analysis Using Tcga Databasementioning
confidence: 97%
“…Further, due to the limitations of biopsy sampling, biopsy grading may be inconsistent with the prostatectomy specimen. 8,9 Therefore, prostate cancer patients with apparently identical morphologies may have different survival rates, partly due to variable subjective observations. However, generally, patients with higher Gleason scores usually have worse prognoses than those with low scores.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitation of prostate tumor stromal changes have demonstrated that this is a useful measure of clinical outcomes, providing additional prognostic information over Gleason grade (McKenney et al, 2016). Seminal work on prostate cancer stromal grading showed that the two groups of tumors that are most aggressive are, 1) those with almost no stromal involvement, these seem to be independent of their microenvironment from early in their pathogenesis; and, 2) tumors that exhibit an abundant stromogenic response, where the stroma appears to be a major contributor to tumor growth and invasion (Ayala et al, 2003).…”
Section: Carcinoma-associated Fibroblastsmentioning
confidence: 99%
“…Seminal work on prostate cancer stromal grading showed that the two groups of tumors that are most aggressive are, 1) those with almost no stromal involvement, these seem to be independent of their microenvironment from early in their pathogenesis; and, 2) tumors that exhibit an abundant stromogenic response, where the stroma appears to be a major contributor to tumor growth and invasion (Ayala et al, 2003). Reactive stroma grading (RSG) is an independent predictive factor for PCa biochemical recurrence and PCa specific death (Ayala et al, 2011, McKenney et al, 2016, Saeter et al, 2015, 2016, Yanagisawa et al, 2007). …”
Section: Carcinoma-associated Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation